ANALISIS RISIKO KESEHATAN LINGKUNGAN (ARKL) AKIBAT PAPARAN KARBON MONOKSIDA (CO) MELALUI INHALASI PADA PEDAGANG DI SEPANJANG JALAN DEPAN PASAR PROJO AMBARAWA KABUPATEN SEMARANG - Rionaldo Elen Pamungkas; Sulistyani Sulistyani; Mursid Rahardjo (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Ambarawa has a total vehicle ownership of 23.999 units and has an area of 28.221 km2. Congestion is often happening on several streets in Ambarawa including the front road of Projo Market Ambarawa. Congestion results in the high concentrations of carbon monoxide pollutants in the ambient air which may pose a risk of health exposure to the traders along the front road of Projo Market.This study aims to determine the condition of environmental health due to the exposure of carbon monoxide through inhalation paths on the traders along the front road of Projo Market Ambarawa. The type of this research is a descriptive research with cross sectional research design and using Environmental Health Risk Analysis (EHRA) approach. The subject sample of this study is obtained by the total sampling method that is amounted to 58 traders along the front road of the Projo Market, with air sampling at 19 point locations. The results showed that carbon monoxide concentrations has a minimum value of 8,47 mg/m3 and a maximum value of 92,53 mg/m3 with an average of 34,35 mg/m3. Average exposure time was 7,35 hours, with an average frequency of exposure 349.7 days, and average duration of 18 years. The results of the analysis were obtained for non-carcinogenic real-time effects: RQ ≤ 1 as much as 53 person (91,4%), RQ > 1 as much as 5 person (8,6%). As for non-carcinogenic lifetime effects, the results are RQ ≤ 1 as much as 53 person (91,4%), RQ > 1 as much as 5 person (8,6%). The conclusion is that the health risk level of non-carcinogenic effects in both real-time and lifetime effects showed that most of the respondents were safe.